2013
DOI: 10.4184/asj.2013.7.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Gorham's Disease of Spine

Abstract: Gorham's disease is a rare disorder characterized by clinical and radiological disappearance of bone by proliferation of non-neoplastic vascular tissue. The disease was first reported by Jackson in 1838 in a boneless arm. The disease was then described in detail in 1955 by Gorham and Stout. Since then, about 200 cases have been reported in the literature, with only about 28 cases involving the spine. We report 2 cases of Gorham's disease involving the spine and review related literature to gain more understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…Sekharappa et al also reported two cases of Gorham's disease of the spine, both presented with the spinal deformity and spinal cord compression symptoms. The lesion was resected surgically and the symptoms removed in both patients after the rehabilitation period [5].…”
Section: Discussionmentioning
confidence: 99%
“…Sekharappa et al also reported two cases of Gorham's disease of the spine, both presented with the spinal deformity and spinal cord compression symptoms. The lesion was resected surgically and the symptoms removed in both patients after the rehabilitation period [5].…”
Section: Discussionmentioning
confidence: 99%
“… 6 To the best of our knowledge, 13 cases of GD of spine have been reported after 2005. 8 20 21 22 23 24 25 26 27 28 29 30 31 A brief review of these cases with treatment and outcome has been shown in Table 2 . Out of the total 41 reported cases of GD of spine, cervical spine is the most commonly affected with 11 cases involving only cervical spine and additional 6 cases involving cervicothoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…The extension of the disease from the ribs, sternum, scapula or vertebrae to the mediastinum, with the invasion of the thoracic duct, can lead to pleural or chylous pericardial effusion, and respiratory and cardiac failure, respectively [18][19][20][21][22]. Paraplegia may occur in cases involving the spine, with vertebral fracture and spinal cord compression [23]. The case we report is mainly characterized by the involvement of the left hip joint, resulting in prominent pain and functional disability of that joint.…”
Section: Discussionmentioning
confidence: 99%